Impact of secret number ice-breaking on elementary students’ Mathematics performance - Achmad Mulyadi; Edi Supriadi (Curricula: Journal of Curriculum Development, 2025)
This study explores the effect of the ice-breaking secret number technique on mathematics learning outcomes among fifth-grade students at SDN Cilangkap 01 Pagi. The research was conducted in response to students’ low motivation and poor performance in mathematics, often caused by monotonous teaching methods. The objective is to examine whether this interactive approach improves learning outcomes. The study used a quasi-experimental design with a pretest-posttest control group. The sample consisted of 60 students divided into experimental and control groups. The experimental class received instruction using the ice-breaking secret number technique, while the control class followed conventional teaching. Data were collected through tests and questionnaires, and analyzed using t-tests and effect size calculations. Results showed a significant improvement in the experimental group's post-test scores and enhanced student engagement, as indicated by questionnaire responses. The findings indicate that the ice-breaking secret number technique positively influences student performance and motivation in mathematics. This method can serve as an effective alternative for primary school teachers to create a more dynamic and participatory learning environment.   Abstrak Penelitian ini mengeksplorasi pengaruh teknik ice-breaking secret number terhadap hasil belajar Matematika murid kelas 5 SDN Cilangkap 01 Pagi. Penelitian ini dilakukan sebagai tanggapan atas rendahnya motivasi dan prestasi murid dalam pelajaran Matematika yang sering kali disebabkan oleh metode pengajaran yang monoton. Tujuannya untuk menguji apakah pendekatan interaktif ini dapat meningkatkan hasil belajar. Penelitian ini menggunakan metode kuasi-eksperimen dengan desain kelompok kontrol pretest-posttest. Sampel terdiri dari 60 murid yang dibagi menjadi kelompok eksperimen dan kelompok kontrol. Kelas eksperimen menerima pengajaran dengan menggunakan teknik ice-breaking secret number, sedangkan kelas kontrol mengikuti pengajaran konvensional. Data dikumpulkan melalui tes dan kuesioner, dan dianalisis menggunakan uji-t dan perhitungan effect size. Hasil penelitian menunjukkan adanya peningkatan yang signifikan pada nilai post-test kelompok eksperimen dan peningkatan keterlibatan murid berdasarkan tanggapan kuesioner. Temuan ini menunjukkan bahwa teknik ice-breaking secret number berpengaruh positif terhadap kinerja dan motivasi murid dalam Matematika. Metode ini dapat menjadi alternatif yang efektif bagi guru sekolah dasar untuk menciptakan lingkungan belajar yang lebih dinamis dan partisipatif. Kata Kunci: hasil belajar Matematika; ice-breaking; murid sekolah dasar